Dampak Transportasi Online pada Kinerja Keuangan Perusahan Transportasi Konvensional - Flafiana Sarihartati Agun; Diyah Sukanti Cahyaningsih (Jurnal Akuntansi dan Perpajakan, 2019)
PT Blue Bird, Tbk and PT Express Transindo Utama are conventional transportation service businesses, this research wants to assess the impact of financial performance as measured by Current Ratio, Cash Ratio, Debt to Asset Ratio, Debt to Equity Ratio, Fixed Asset Turn Over, Total Asset Turn Over, Net Profit Margin, Return on Assets, Return on Equity, Earning Per Share, and Price Earning Ratio before and after the emergence of online transportation. The data used is the 2012-2017 financial statements. With descriptive quantitative analysis the results are presented. at PT Express Transindo Utama, Tbk. shows that Current Ratio, Cash Ratio, Debt to Equity Ratio, Debt to Asset Ratio, Fixed Asset Turn Over, Total Asset Turn Over, Net Profit Margin, Return On Asset, Return On Equity, Earning Per Share and Price Earning Ratio have decreased after the advent of online transportation. The results of research at PT Blue Bird, Tbk. shows that Fixed Asset Turn Over, Total Asset Turn Over, Net Profit Margin, Return On Asset, Return On Equity, Earning Per Share and Price Earning Ratio decreased after the advent of online transportation. While Current Ratio, Cash Ratio, Debt to Asset Ratio, Debt to Equity Ratio increased. It was concluded that the emergence of online transportation does not always have a negative impact if conventional transportation service companies are able to adaptation